Antipyretics and Febrile Seizure Recurrence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The efficacy of antipyretic agents in prevention of febrile seizures was examined in a randomized, placebo-controlled, double-blind trial at various hospitals in Finland.